Oportunidades e desafios para a utilização de soluções baseadas na natureza no combate de inundações urbanas na cidade de São Paulo/ SP-Brasil - Rodrigues, Maria Santiellas Costa (2021)
The rapid and disorderly growth of the urban population, added to the effects of climate change, have increased the occurrences and intensities of phenomena related to urban flooding, affecting the sustainability of urban areas and negatively impacting the social, environmental, and economic spheres of many cities. Because of such impacts, many cities work on traditional procedures to face them, among which the so-called gray solutions stand out. On the other hand, there is a growing number of Chinese, European and American cities that, according to the recommendations of the United Nations and with global concerns regarding sustainable development, have adopted nature-based solutions (SBN's) to combat the negative effects caused by such phenomenon. Given this paradox and considering the increase of occurrences of floods in the city of São Paulo, in recent decades, this dissertation aims to analyze the opportunities and challenges of inserting SBNs in the fight against urban floods in the city of São Paulo. This is an applied research, exploratory in nature, and based on a bibliographic survey, document analysis, and semi-structured interviews with professionals from agencies involved in managing the fight against urban floods. The results obtained allowed the identification of opportunities for actions by SBN's that can support flood control, improving water and green space management, as well as climate resilience, increased infiltration, collection, and storage of water. Regarding the challenges, the results pointed to cultural issues, the size of the area needed for projects of this type, financial and managerial issues, and difficulties in measuring and evaluating the adopted solutions. The research points to the importance of combining green and gray solutions in combating urban floods, which allows better use of the benefits that each one of them can offer. It is expected that the presented results will contribute to future public drainage policies aimed at combating urban flooding in the city of São Paulo and for other studies aimed at the challenges observed in this research.